Phonological Interference in the Pronunciation of the Latin Script and Dictation Performance among BIPA Learners with Non-Latin Script Backgrounds (Thailand–Cambodia) - Dian Arsa; Ananda Putriani (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the forms and causal factors of phonological interference in the pronunciation of the Latin alphabet and to examine their impact on the dictation performance of Indonesian as a Foreign Language (BIPA) learners from non-Latin script backgrounds. The data consist of pronunciation errors and dictation writing errors, specifically problematic phonemic and vowel contrasts. The results show phonological interference in the form of voiced–voiceless consonant substitutions (b–p, g–k, t–d, s–z), affricate confusion (c–j), liquid consonant interchange (r–l), reduction of mid–high vowel contrasts (e–i), and reduction of back vowel contrasts (o–u). This interference is apparent simultaneously in spoken production and in the written form of dictation, indicating a disruption in phonemic perception rather than merely in articulation. The primary causes of this interference lie in the differences between the phonological systems of the learners’ native languages (Thai and Khmer) and Indonesian; the differences in script systems (non-Latin versus Latin); and the phonological transfer from English as an intermediary language and source of Latin letter pronunciation patterns. The proposed pedagogical implication is the need to reinforce the stage of script familiarization as a process of phonological reconstruction through minimal pair exercises, phonemic perception training, articulatory exercises, and the regular use of diagnostic dictation exercises.